Kucing Sebagai Ide Penciptaan Seni Grafis - Auryn Hidayana Brifia; Asra Ilal Khairi (Departement of Mathematics Education, 2024)
This final work aims to visualize cats as an idea for creating graphic art with the limitations of creating colors, gestures and their cute nature. The method used is first, the preparation stage, namely conducting observations and gathering information. Second, the elaboration stage, namely the in-depth stage by describing all the data, Ketoga, the synthesis stage by matching the themes. Fourth, the realization stage by copying sketches into clichés, preparing tools and work processes. The fifth stage of completion is improving the work. The work entitled: (1) Playing happily (2) Deep sleep (3) Licking (4) Stretching (5) Carrying a child (6) Chasing mice (7) Climbing a tree (8) Private Moment (9) Hungry King (10) Look for something to eat.